2008
DOI: 10.1203/pdr.0b013e318174eff8
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of Congenital Cystic Adenomatoid Malformation Reveals a Novel Pulmonary Gene: Fatty Acid Binding Protein-7 (Brain Type)

Abstract: ABSTRACT:The pathogenesis of congenital cystic adenomatoid malformation (CCAM) is unknown and its natural history is unpredictable. Fatty acid binding protein-7 (FABP-7) has been previously described in brain and breast development, but never before in the lung. We investigate gene expression in CCAM, and hypothesize that CCAM results from an aberration in the signaling pathway during lung development. Under IRB approval, tissue specimens of fetal CCAM, fetal control, postnatal CCAM, and postnatal control were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 29 publications
2
12
0
Order By: Relevance
“…Another candidate gene is the fatty acid-binding protein FABP-7 [34], the expression of which is reduced in foetal CPAM specimens. An overexpression of Clara cell marker 10 was also identified [13].…”
Section: Histopathology and Geneticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another candidate gene is the fatty acid-binding protein FABP-7 [34], the expression of which is reduced in foetal CPAM specimens. An overexpression of Clara cell marker 10 was also identified [13].…”
Section: Histopathology and Geneticsmentioning
confidence: 99%
“…2 Genes implicated in CPAM, PPB and BAC [14,30,31,32,33,34,35,127,137,138,139,140,141,142,143]. TTF1 = Thyroid transcription factor 1; PDGF-B = platelet-derived growth factor B; FABP-7 = fatty acid-binding protein 7; GDNF = glial cell-derived neurotrophic factor; Shh = sonic hedgehog; FGFR2b = FGF receptor-2b; FHIT = fragile histidine triad; Rb = retinoblastoma protein; EGFR = epidermal growth factor receptor. …”
Section: Managementmentioning
confidence: 99%
“…FABP7 is an intracellular lipid-binding protein, involved in long-chain fatty acids transport and cell proliferation [43]. It may be involved in abnormal pulmonary development, since lower expression of FABP7 was found in patients with congenital cystic adenomatoid malformation [44]. In addition, higher expression of FABP7 was seen in clear cell renal cell carcinoma and the authors suggested that the gene activates the ERK and STAT3 signalling pathways [45].…”
Section: Discussionmentioning
confidence: 99%
“…The disease is characterized by proliferation of pseudoglandular bronchial structures, formation of multiple cysts in the terminal bronchioles, and lack of alveolar development 4 . Stocker classification of CPAM includes five subtypes: type 0, lesions are composed of bronchial‐like tissue; type I, single or multiple large cysts (>2 cm in diameter); type II, multiple small cysts (<1 cm in diameter); type III, solid and microcystic lesions; and type IV, lesions of more distal acinar origin 5 . The condition does not regress after birth, and the development of fetal hydrops is associated with an increased risk of death 6 .…”
Section: Introductionmentioning
confidence: 99%